Yanawana Pedagogies: Learning with Coahuiltecan Water Teachings - Muñoz, Marissa Aki'Nene; Montes, Pablo; Villanueva, Marleen (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
In honor of the place where we were visiting, Marleen woke early in the morning to collect Water from the nearby Great Lake, and we lovingly created a makeshift altar of fresh flowers and rebozos. We opened the circle with a public song about sacred Water, then moved on to introductions: “Please share your name, pronouns, and which Waters hold you as your home.”Some folks chose lakes, oceans, rivers, some shared a name in English, some named their home Waters by their ancestral languages. As a collective, we took in a deep breath, and dropped down into our bodies, and into relational ways of knowing and being in community. We were ready to begin.As Indigenous educators, we are responsible and response-able (Kuokkanen, 2007) to our home communities, to our human and more-than-human kin (Nxumalo & Villanueva, 2020) and to each other to follow cultural protocols that prepare us for our work. In this paper, we reflect on our learning journeys, discussing our roles as Water protectors, mothers, community organizers, and scholars, and offer three examples of ongoing Water work.